2022
DOI: 10.12973/eu-jer.11.2.847
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction as the Mediator Between a Learning Organization and Organizational Commitment Among Lecturers

Abstract: <p style="text-align: justify;">The higher educational institution needs a group of dedicated and committed lecturers to endure the institution during these turbulent times. As the organizational commitment reflects the self-identification of an employee with the organization, it has far-reaching implications on multifarious aspects in the organization. This present study investigated whether job satisfaction could mediate the relationship between learning organization and organizational commitment. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…For example, Yulius (2022) and Basri et al (2021) demonstrated that visionary leadership significantly affects organizational commitment. Wang and Rashid (2022) also proved that strategic leadership is related to organizational commitment. This suggests that visionary leadership is a good predictor of organizational commitment, including in school organizations.…”
Section: Visionary Leadership and Organizational Commitmentmentioning
confidence: 88%
“…For example, Yulius (2022) and Basri et al (2021) demonstrated that visionary leadership significantly affects organizational commitment. Wang and Rashid (2022) also proved that strategic leadership is related to organizational commitment. This suggests that visionary leadership is a good predictor of organizational commitment, including in school organizations.…”
Section: Visionary Leadership and Organizational Commitmentmentioning
confidence: 88%
“…The term "organizational support" comes from the field of organizational psychology and describes the degree to which workers think that their employers care about them and respect the contributions they make to the company (Conway, 2015). It plays a pivotal role as a precursor to a variety of employee outcomes, including work satisfaction, organizational commitment, and desire to leave the company (DeConinck et al, 2017;Nazir & Islam, 2017;Panaccio & Vandenberghe, 2009;Wang & Rashid, 2022). Self-report surveys are the most common method for calculating POS (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all information technology firms continue to produce a significant amount of money from Application Development and Maintenance (ADM). Software companies are rapidly rising the software value chain as greater competition, cheaper billing rates, and commoditization [16][17] [18] of lower-end ADM services result in a reduction [19] in the cost of doing business. High-value-added services provided by the industry include consulting, product development and research & development, social media, mobile, analytics; cloud computing [20], and turnkey solutions that are provided end-to-end.…”
Section: • Size Of the Industry • Mergers And Acquisitionsmentioning
confidence: 99%